Quality attributes of composite flour of white finger millet (Eleusine coracana) and wheat (Triticum aestivum) for bread dough preparation - A, Ashwini; J, Prashanth S; Jammanakatti, Savita V; Nayak , Shruti (Journal of Postharvest Technology, 2022)
The composite flour was developed by blending refined wheat flour (WF) with varying proportions of white ragi flour (WRF) in the ratio of 80:20, 60:40, 50:50, 40:60, and 20:80 respectively. A few important parameters were evaluated for the suitability of white ragi flour as gluten replacers or as composite flour in the bakery industry. The physical and chemical characteristics of wheat flour and white ragi flour (KMR 340 variety) along with the different ratios were evaluated. The chemical characteristics viz, Ash, Carbohydrates, Crude fibre, Energy values, Fat, Proteins, and Moisture content of wheat flour and white ragi flour were analysed and found 8.56%, 9.38 g, 1.20 g, 2.09 g, 0.90 g, 79.77 g per 100 g and energy was found to be 363 K cal/g compared to 358 Kcal/ g, the Fat, Total ash, Crude fibre and Carbohydrates were high in comparison to the wheat flour and the content of protein was low in contrast with wheat flour but was in the range which can be contrast to medium strong wheat flour used for fermented bakery products purposes, few mineral content was also high, these superior nutritional aspects with physical characteristics such as color, whiteness index, low water activity in the range of 0.6-0.7, moisture content in the range of 8-10%, elevated total ash content (1.6-2.0%) and not much variations in the dough rheology aspects, true density, pH, untapped bulk density values varied from 0.52 to 0.57 and tapped bulk density values were increasing from 0.69 to 0.71 of composite flours with comparable porosity values of 21-26% has been a key factors for exploring the white ragi flour for value addition purposes. With this background, investigations were taken to develop composite bread from wheat flour blended with white ragi flour. Therefore the present work was taken up to examine different attributes of composite flour by blending wheat flour with white ragi flour to identify its potential application in different bakery products such as bread.